Optical Coherence Elastography-Based Corneal Strain Imaging During Low-Amplitude Intraocular Pressure Modulation - Kling, Sabine (Front Bioeng Biotechnol, 2020)
Purpose: Optical coherence elastography (OCE) is a promising technique for high-resolution strain imaging in ocular tissues. A major strain-inducing factor in the eye is intraocular pressure (IOP), with diurnal physiological fluctuations reaching up to 5 mmHg. We study herein low-amplitude IOP modulation to assess local corneal strain patterns. Methods: Ex vivo porcine eye globes were adjusted to an initial IOP of 15 mmHg and subsequently 25 mmHg. Corneal strain was induced by two subsequent pressure cycles, in which IOP was first increased and then decreased, each by a total of 5 mmHg. Two-dimensional optical coherence tomography (2D-OCT) B-scans were recorded after each loading step. Axial strain maps were obtained from magnitude and phase changes and supra-pixel displacements from cross-correlation. The strain detection sensitivity was evaluated in an isotropic material. Results: Deformations arising from a single 1-mmHg step could be resolved. The largest strain amplitudes (5.11·10(−3)) were observed in the posterior stroma at a low initial IOP. Strain amplitude was 1.34 times higher at 15 mmHg than at 25 mmHg (p = 0.003). Upon IOP increase, the anterior cornea was compressed, whereas the posterior cornea showed axial expansion. Both morphological images and strain maps were sensitive to postmortem time. Strains that are larger than 2.44·10(−5) could be reliably measured. Conclusions: Low-amplitude IOP modulation, similar to diurnal physiological changes, induced measurable deformations in corneal tissue. Axial strain maps permit a localized comparison of the corneal biomechanical response. Small-strain OCE can likely be extended to other domains.